Platelet Count as a Marker of Thrombosis Risk in Male Athlete Smokers Aged 17–20 Years - Maulidya May; Heri Purnama Pribadi (Journal of Strength and Conditioning, 2025)
Platelets play a crucial role in hemostasis and blood clot formation, contributing to vascular stability. Cigarette smoking is known to increase oxidative stress, which may impair endothelial function and promote platelet activation. In athletes, regular physical training induces physiological adaptations that help regulate hematological balance, whereas smoking exposure introduces reactive oxygen species that may increase thrombotic potential. This study aimed to compare platelet counts among three groups of young males: athlete smokers, athlete non-smokers, and non-athlete controls aged 17–20 years. A total of 33 participants were selected using purposive sampling, with 11 individuals in each group. Venous blood samples were collected from the cubital vein and analyzed using a hematology analyzer. Data normality was assessed using the Shapiro–Wilk test, and group differences were analyzed using one-way ANOVA with a significance level of 0.05. The highest mean platelet count was observed in athlete non-smokers (380.65 ± 138.31 ×10³/µL), followed by the control group (328.48 ± 65.11 ×10³/µL) and athlete smokers (276.20 ± 64.61 ×10³/µL). Statistical analysis revealed no significant differences among groups (p = 0.096). These findings suggest that regular physical activity may help maintain platelet stability in young athletes despite smoking habits; however, the potential long-term risk of thrombosis associated with smoking should be considered.